Pflege und Pflegekosten in der Zukunft – Brauchen wir mehr Versicherungsschutz? - Iris Kesternich; André Romahn; Johannes Van Biesebroeck; Marjolein van Damme (Wirtschaftsdienst, 2024)
We evaluate the effect of supplementary long-term care insurance, which would limit the costs of a stay in a care facility. A higher long-term care insurance subsidy reduces the costs of a stay in a care facility and increases the welfare of those in need of care. However, falling costs could lead to people in need of care switching from outpatient care to in-patient facilities, which would cause costs to rise sharply and exceed the welfare gains. The main beneficiaries of higher subsidies are unmarried people and those in need of care with very low and high incomes. A flat-rate subsidy would be preferable to a percentage-based subsidy.
Keywords: I11; I38; L13; H51; 330